A prediction model for peak power output from different incremental exercise tests - Luttikholt, H.; McNaughton, L.; Midgley, A. W.; Bentley, D. J. (International Journal of Sports Physiology and Performance, 2006)
There is currently no model that predicts peak power output (PPO) thereby allowing comparison between different incremental exercise test (EXT) protocols. In this study we have used the critical power profile to develop a mathematical model for predicting PPO from the results of different EXTs. Purpose: The purpose of this study was to examine the level of agreement between actual PPO values and those predicted from the new model. Methods: Eleven male athletes (age 25 ± 5 years, VO2max 62 ± 8 mL · kg-1 · min-1) completed 3 laboratory tests on a cycle ergometer. Each test comprised an EXT consisting of 1-min workload increments of 30 W (EXT30/1) and 3-min (EXT25/3) and 5-min workload increments (EXT25/5) of 25 W. The PPO determined from each test was used to predict the PPO from the remaining 2 EXTs. Results: The differences between actual and predicted PPO values were statistically insignificant (P > .05). The random error components of the limits of agreement of £30 W also indicated acceptable levels of agreement between actual and predicted PPO values. Conclusions: Further data collection is necessary to confirm whether the model is able to predict PPO over a wide range of EXT protocols in athletes of different aerobic and anaerobic capacities.